2018
DOI: 10.1016/j.chemosphere.2018.03.121
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of dermal exposure to chlorpyrifos among applicators on rice farms in Ghana

Abstract: Generally, there is limited information on pesticide absorbed dose levels and health risk attributable to the dermal route of exposure among applicators. The objective of this study was to evaluate the absorbed dose levels and consequent health risk from dermal exposure to chlorpyrifos among applicators on rice farms in Ghana. The whole-body dosimetry technique was used to capture chlorpyrifos residues penetrating the applicators' clothing and reaching their skin, as well as residues reaching uncovered body ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Exposure to pesticides poses one of the most important occupational risks to farmers in countries in the Global South (e.g., [ 1 , 2 , 3 , 4 , 5 ]), being associated with a wide range of symptoms and disorders including respiratory problems, metabolic disorders, neurodegenerative diseases or cancer (e.g., [ 6 , 7 , 8 , 9 ]) aside from several biomarker changes (e.g., [ 10 , 11 , 12 ]). Identification of the hazards of pesticide use and the establishment of safe methods of pesticide handling is a challenge for occupational health and safety (see [ 13 ] for regulations or [ 14 ] for safety training).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to pesticides poses one of the most important occupational risks to farmers in countries in the Global South (e.g., [ 1 , 2 , 3 , 4 , 5 ]), being associated with a wide range of symptoms and disorders including respiratory problems, metabolic disorders, neurodegenerative diseases or cancer (e.g., [ 6 , 7 , 8 , 9 ]) aside from several biomarker changes (e.g., [ 10 , 11 , 12 ]). Identification of the hazards of pesticide use and the establishment of safe methods of pesticide handling is a challenge for occupational health and safety (see [ 13 ] for regulations or [ 14 ] for safety training).…”
Section: Introductionmentioning
confidence: 99%
“…Liver failure, alteration of entry routes (skin, respiratory tract and eyes) have been so far reported in neighboring villages with similar agricultural practices by Sonchieu et al [4]. The hygienic variation of body care challenge after spraying generally affects the heath of operators: the more the bathing period extends the longer the contact time and the more toxicants penetrate the body [1]. Pesticides enumerated by Sonchieu et al (2018) [8] are also used here and are mostly involved in symptoms and signs mentioned in the study which is on the same line with the study carried-out by Mejía et al [15].…”
Section: Discussionmentioning
confidence: 81%
“…Health problems related to the use of pesticides have been reported worldwide, but in developing countries, the misuse of pesticides is regularly reported mainly in areas where vegetables and industrial crops are cultivated. This poor application, generally, if prolonged, will be induced, it will induce chronic health effects such as developmental and neurobehavioral anomalies, Farmers with Chronic Kidney Disease [1] [2]. Commonly, exposure to pesticides occurs mainly through three main routes: skin, nostrils and mouth [1], Atabila et al [1] reported that, with agricultural applicators, the dermal route is usually the most prominent exposure route.…”
mentioning
confidence: 99%
“…The team measured how much pesticide residue passed through the workers' clothing to contact their skin. From those data, they calculated that many of the workers absorbed a dose of the pesticide that was several times higher than the dose known to increase risk of developing acute adverse health effects such as confusion and intestinal distress 5 . Pesticides have long been linked to a variety of skin conditions, including contact dermatitis, acne and even melanoma.…”
Section: Mapping the Exposure Landscapementioning
confidence: 99%